2016
DOI: 10.1007/s11357-016-9947-5
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated reduction of serum thyroxine and hippocampal histone acetylation links to exacerbation of spatial memory impairment in aged CD-1 mice pubertally exposed to bisphenol-a

Abstract: Age-related cognitive decline has been associated with changes in endogenous hormones and epigenetic modification of chromatin, including histone acetylation. Developmental exposure to endocrine disrupting chemicals, such as bisphenol-A (BPA) that produces endocrine disruption and epigenetic changes, may be a risk factor for accelerating cognitive deficits during aging. Thus, we exposed CD-1 mice to BPA (0, 1, and 100 mg/l BPA in the drinking water) orally during puberty (from postnatal days 28 to 56) and inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Decreased levels of circulating TH occur with ageing in humans (Chakraborti et al, 1999) and rodents (Cao et al, 2012), and have also been observed in non-mammals, including birds (Carr and Chiasson, 1983). Many studies have shown declines in the hippocampal process of spatial memory assimilation in aged humans, rodents, or monkeys (Foster et al, 2012;Jiang et al, 2016). This process is well established as being particularly sensitive to decreases in TH availability (Correia et al, 2009;Ge et al, 2015).…”
Section: Roles Of Th In the Ageing Brainmentioning
confidence: 98%
See 1 more Smart Citation
“…Decreased levels of circulating TH occur with ageing in humans (Chakraborti et al, 1999) and rodents (Cao et al, 2012), and have also been observed in non-mammals, including birds (Carr and Chiasson, 1983). Many studies have shown declines in the hippocampal process of spatial memory assimilation in aged humans, rodents, or monkeys (Foster et al, 2012;Jiang et al, 2016). This process is well established as being particularly sensitive to decreases in TH availability (Correia et al, 2009;Ge et al, 2015).…”
Section: Roles Of Th In the Ageing Brainmentioning
confidence: 98%
“…This could be something to consider in the context of impaired neurogenesis caused by BPA exposure, during both perinatal periods and adulthood (Tiwari et al, 2015a;Tiwari et al, 2015b). Exposure to BPA during puberty can also impair spatial cognitive abilities in adult mice (Jiang et al, 2016). Besides, EE2 exposure during adulthood has been shown to disrupt cell proliferation in neurogenic niches of mice (Brock et al, 2010;Ormerod et al, 2003) and zebrafish (Diotel et al, 2013).…”
Section: Evolutionary Implications Of Endocrine-disrupting Chemicals mentioning
confidence: 99%
“…The capacity of BPA to interfere with THR transcription activity has been analyzed by several studies, with some of them showing interference at the nuclear transcriptional level, particularly for T3-related genes (Xu et al 2007, Heimeier et al 2009, Hansen et al 2016, Jiang et al 2016, and one study demonstrated interference at a nongenomic level (Sheng et al 2012). BPA and several BPA analogs that have recently been introduced in the plastics industry were tested on different TH-responsive cell lines (GH3, FRTL-5 and rat cerebellar cells), and the results showed that they interfered with the expression of genes involved in TH synthesis (Slc5, Tg and Tpo), thyroid cell activity/ proliferation (Tshr, Tshb, Thrb, Thra, Dio1 and Dio2) and thyroid transcriptional regulation (Pax8, Nkx2-1 and FoxE1) (Gentilcore et al 2013, Lee et al 2017.…”
Section: Plasticizersmentioning
confidence: 99%
“…Studies with pregnant ewes, which have a gestational period more comparable to that of humans, that were exposed to BPA both subcutaneously and by dietary exposure demonstrated lower levels of THs in pregnant females and newborns, and those females showed evidence of a modified deiodination balance (Viguie et al 2013, Guignard et al 2017. In analyzing other windows of exposure, mice exposed to BPA during puberty have been shown to have lower free T4 levels (Jiang et al 2016).…”
Section: Plasticizersmentioning
confidence: 99%
“…It is still unclear whether exposure to BPA and its derivatives can cause hypothyroidism due to limited evidence. A decrease in T4 levels was found in male and female adult rodents [110,113,114] and in rat pups of both sexes [114] or with a sex-specific effect [112,115]. The competition of BPs with TTR, as observed in vitro [70,84,92], resulting in a portion of serum T4 displaced from TTR, could determine an increased rate of T4 metabolism and elimination and the consequent reduction of T4 circulating levels [110].…”
Section: Rodentsmentioning
confidence: 95%